Sedation-Only Anesthesia for Pediatric Circumcision: A Safer Alternative - Ozdes, A. A.; Korhan, Z.; Beler, M.; Canturk, R.; Ozan, T. (Wolters Kluwer Medknow Publications, 2025)
Background:Pediatric circumcision is a common procedure, and effective pain control is essential for recovery and comfort. The optimal anesthesia technique remains debated.Aim:To compare the efficacy and safety of sedation-only anesthesia versus sedation combined with local lidocaine infiltration anesthesia in children undergoing circumcision.Methods:In this prospective study, 140 boys aged 1-6 years were randomly assigned to receive either intravenous sedation alone (Group I) or sedation plus local anesthesia (Group II). Both groups received a standardized sedative regimen: midazolam, propofol, fentanyl, and ketamine. Postoperative pain was assessed at 1 and 3 hours using the FLACC scale. Complications were recorded.Results:Median FLACC scores at both 1 hour (Group I: 2.0 [0-6], Group II: 2.0 [0-6]) and 3 hours (Group I: 1.0 [0-4], Group II: 1.0 [0-3]) showed no significant difference (P > 0.05). However, local complications such as ecchymosis and edema were more frequent in the group receiving local anesthesia (Group II: 7.1%) compared to the sedation-only group (Group I: 15.7%).Conclusions:Sedation-only anesthesia using midazolam, propofol, fentanyl, and ketamine provides effective postoperative pain control for pediatric circumcision, with fewer local complications than when combined with local infiltration anesthesia.
Keywords: Circumcision; local anesthesia; pediatric anesthesia; postoperative pain; sedation analgesia